2023
DOI: 10.3389/fpsyg.2022.1093999
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 risk perception on pro-environmental behavior of Chinese consumers: Perspectives from affective event theory

Abstract: IntroductionCOVID-19 has altered human cognition and changed the cultural values of society. However, there has not been much debate among scholars about whether these above changes have led to an increase in pro-environmental behavior (PEB) of Chinese consumers.MethodsA comprehensive model was developed based on affective event theory. An online questionnaire was distributed, and 501 usable questionnaires were collected. In addition, two complementary approaches were employed: partial least squares structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 166 publications
0
1
0
Order By: Relevance
“…Initially, to assess collinearity, the variance inflation factors (VIFs)for all predictive constructs in the structural model were examined. As depicted in Table 5,all VIF values were between 1.0 and 1.341,which is substantially below the cut-off value of 3,establishing that collinearity did not pose an issue in the model (Jie et al, 2022;Xu et al, 2019;Zhou, 2022;.Following this, bootstrapping, utilizing 5000subsamples,was conducted to evaluate the hypothesis significance (Tahlyan et al, 2022). The results indicated that the majority of the paths reached statistical significance at the 0.05 level, thus validating most of the proposed hypotheses.…”
Section: Inspecting the Inner Structural Modelmentioning
confidence: 65%
“…Initially, to assess collinearity, the variance inflation factors (VIFs)for all predictive constructs in the structural model were examined. As depicted in Table 5,all VIF values were between 1.0 and 1.341,which is substantially below the cut-off value of 3,establishing that collinearity did not pose an issue in the model (Jie et al, 2022;Xu et al, 2019;Zhou, 2022;.Following this, bootstrapping, utilizing 5000subsamples,was conducted to evaluate the hypothesis significance (Tahlyan et al, 2022). The results indicated that the majority of the paths reached statistical significance at the 0.05 level, thus validating most of the proposed hypotheses.…”
Section: Inspecting the Inner Structural Modelmentioning
confidence: 65%
“…Initially, to assess collinearity, the variance inflation factors (VIFs) for all predictive constructs in the structural model were examined. As depicted in Table 6, all VIF values were between 1.0 and 1.341, which is substantially below the cut-off value of 3, establishing that collinearity did not pose an issue in the model [116][117][118][119]. Following this, bootstrapping, utilizing 5000 subsamples, was conducted to evaluate the hypothesis significance [125].…”
Section: Inspecting the Inner Structural Modelmentioning
confidence: 92%
“…The indicators for perceived self-efficacy (PSE) were formulated based on the range described by Wu et al [115], including five items. Purchase intention (PI) measures were developed following the work of [116][117][118][119], and Shen et al (2022), comprising four items. Each item was evaluated using a 5-point Likert scale ranging from "strongly disagree" to "strongly agree".…”
Section: Measures and Data Analysismentioning
confidence: 99%